PROMOTING LECTURER’S IELTS SCORE THROUGH SUPER INTENSIVE (SUPIN) IELTS PREPARATION PROGRAM - Krisna Satria Perbowo; Bita Dwi Rahmani; Trisna Roy Pradipta (Universitas Lambung Mangkurat, 2018)
One of the efforts to improve language skills of the lecturers is by joining IELTS Preparation program organized by one of the International Education institution (IEDUC) located in Bandung. This research aims to find out whether there is a correlation between the results of the Super-IELTS Intensive program (SUPIN) lecturer final score with the real International Test score in sort of the evaluation process on that program. The subject was taken from two classes program comprising 19 lecturers as participants. The data in this study were obtained from the pre and post-test score during SUPIN program and the score on the real International test conducted by the British Council. The result of the research revealed the fact that listening test obtained the highest gain while speaking got the lowest gain during the program. The further analyzing on Variance got a significant linear regression by having 0.959 as a coefficient correlation. It means that there is a significant correlation between final score of SUPIN program (X) and International test score (Y) which contribute 92.1% toward the International test score. Meanwhile, only 7.9% was contributed by other factors. In other words, the SUPIN program is effective to increase Lecturer’s skill on doing IELTS test.